Physiological and Immune Functions of Punicalagin - Venusova, Eva; Kolesarova, Adriana; Horky, Pavel; Slama, Petr (Nutrients, 2021)
The aim of this publication is to compile a summary of the findings regarding punicalagin in various tissues described thus far in the literature, with an emphasis on the effect of this substance on immune reactions. Punicalagin (PUN) is an ellagitannin found in the peel of pomegranate (Punica granatum). It is a polyphenol with proven antioxidant, hepatoprotective, anti-atherosclerotic and chemopreventive activities, antiproliferative activity against tumor cells; it inhibits inflammatory pathways and the action of toxic substances, and is highly tolerated. This work describes the source, metabolism, functions and effects of punicalagin, its derivatives and metabolites. Furthermore, its anti-inflammatory and antioxidant effects are described.
Keywords: immune cells; Immunosuppressive Agents; Ellagic Acid; kyselina ellagová; Hydrolyzable Tannins; ellagic acid; biologická dostupnost; Animals; lidé; proliferation; Humans; hydrolyzovatelné taniny; zvířata; Biological Availability; Metabolome; apoptosis; antiflogistika; punicalagin; metabolom; Anti-Inflammatory Agents; imunosupresiva; metabolism